(3TM GdYhGed GdcHjQs - (3eMeO Hf gdGds ((3SdjeGf Hf MSjf LdHjs)
(3ChdgG (B:s
(3fMeOc jG ef TQM UOhQfG deYQaI cdGe GdYQH(B... (3hHYO abO SCdfj ef dG jSYfj eNGdaJg Cf CTQM GdYhGed aj GdfMh(B... (3bGd GdTjN(B...s
(3BNQgG (B:s
(3hef bGd Cf GdYGed aj GdeVGQY faS GdJLQO hGdeVGQYI aGdYGed eYfi agPg eFI YGed adG jSJZfj GdUZjQ (B... (3hdG jSJZfj GdcHjQ (B... (3hgPG BNQ eG CQOfGg ef TQM GdYhGeds
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdfMhs